The responses of rice plant to tricyclazole at the transcriptome and metabolome levels - Huang, Wengong; Shi, Dongmei; Cheng, Aihua; Chen, Guofeng; Liu, Feng; Zhang, Xiaobo; Dong, Jiannan; Lan, Jing; Ren, Hongbo; Guo, Wei; Liu, Baohai (Frontiers in Plant Science, 2026)
IntroductionTricyclazole is widely employed as a pesticide for controlling rice blast. While effective, it simultaneously acts as a stressor on rice plants.MethodsRice seedlings were treated with tricyclazole for 7 days, and the root and shoot samples were collected for analysis. Four biomarkers of oxidative stress, including SOD, CAT, POD, and MDA were measured to evaluate the physiological responses. Integrated transcriptome and metabolome analysis was performed to reveal the mechanisms underlying the tricyclazole-induced stress response.ResultsTricyclazole significantly increased the levels of SOD, CAT, POD, and MDA in the root and shoot of rice. A variety of differential metabolites and differentially expressed genes (DEGs) were identified, which exhibited diverse functionalities. Flavonoid biosynthesis, glutathione metabolism, and phenylpropanoid biosynthesis were three important metabolic pathways in response to tricyclazole. These pathways encompassed many important metabolites and regulatory genes involved in stress responses. In addition, D-mannose, hispidulin-8-C-glucoside, dicumarol, and 4-hydroxyderricin in the root, and S-Adenosyl-L-methionine, nicotinate D-ribonucleoside, luteolin-7-O-(3'-O-coumaroyl) sophorotrioside, and D-Arabinono-1,4-lactone in the shoot were key metabolites involved in self-detoxification and resistance development of rice against tricyclazole. At the molecular level, these metabolites could be regulated by various DEGs involved in the systemic acquired resistance and response to toxic substances.DiscussionA coordinated molecular and metabolic reprogramming triggered by tricyclazole enables the rice plant to mitigate stress and develop resistance.